'Minding the Koran' in Civil War America: Islamic Revelation, US Reflections. Issue 3 (October 2014) - Einboden, Jeffrey
Abstract : Islamic influences have increasingly gained recognition as vital to early US Literature. Contrary to current critiques of 'Orientalism', however, this essay emphasises the personal, rather than the political, implications of American interest in the Qur'an. Taking its cue from Walt Whitman's iconic 'Song of Myself' – in which the poet characterises himself as 'minding the koran' – the present essay explores the interiority of antebellum approaches to Islam, reading the reflective artistry catalysed by the Qur'an in the young republic. Targeting the year 1855 – not only the date of 'Song of Myself', but also the climax of American Romanticism – I survey 'mindful' engagements with the Muslim scripture pursued simultaneously by American literary celebrities such as Whitman and Melville, as well as anonymous authors writing in the US press.